Discussions A - Z : - Wallwork, Adrian (Cambridge University Press, 1997)
Discussions A-Z is a photocopiable resource book of speaking activities designed to encourage lively, natural discussion among advanced level students. Providing a refreshing perspective on many common themes the material consists of 26 topic-based units, each filled with a variety of stimulating activities